Livestock Evacuation and Emergency Preparedness During Floods: Evakuasi Ternak Selama Bencana Banjir - Nurmeiliasari, Nurmeiliasari; Fenita, Yosi; Bilyaro, Woki; Azis, Arif Rahman; Hermansyah, K. (BPFP Universitas Bengkulu, 2025)
Flooding is a serious threat to the livestock sector that can cause significant economic losses and threaten livestock welfare. This article examines comprehensive strategies for livestock evacuation and emergency preparedness during floods, aiming to minimize such negative impacts. Through a systematic literature review from reputable scientific databases such as PubMed, Scopus, Web of Science and Google Scholar, this study identifies best practices for handling livestock evacuation during floods. The results showed five key components in effective livestock evacuation management: (1) pre-disaster stage that includes risk mapping and identification of flood-prone zones, (2) development of a structured evacuation plan that considers livestock characteristics and available infrastructure, (3) solid coordination between farmers, local government and relevant agencies, (4) implementation of regular evacuation training and simulation, and (5) post-evacuation recovery strategy. The main challenges identified include limited infrastructure, lack of coordination between institutions, and the lack of awareness of farmers on the importance of disaster preparedness. This study recommends the development of an integrated early warning system, capacity building of farmers through continuous training, and strengthening coordination between stakeholders. Implementation of these recommendations is expected to improve the effectiveness of livestock evacuation during floods and reduce potential economic losses and negative impacts on livestock welfare.